2019
DOI: 10.1111/dth.12991
|View full text |Cite
|
Sign up to set email alerts
|

Clapo Syndrome: Effective Response to Treatment With Oral Rapamycin

Abstract: CLAPO syndrome (Capillary vascular malformation of the lower lip, Lymphatic malformations of the head and neck, Asymmetry and Partial or generalized Overgrowth) is a nonfrequent pathology. This syndrome is characterized by the capillary malformation (CM) of the lower lip, a very important clinical sign when diagnosing CLAPO. The aim of our report is to demonstrate that rapamycin could be a reliable and safe targeted therapy in lymphatic malformations (LMs). This drug is useful in reducing the LM's size before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In one study each, 3.5–6 ng/mL [ 30 ], 4–8 ng/mL [ 21 ], 4–10 ng/mL [ 38 ], 4–13 ng/mL [ 36 ], 5–12 ng/mL [ 33 ], 10–12 ng/mL [ 27 ], 10–13 ng/mL [ 19 ] and 12–20 ng/mL [ 35 ] were the target concentrations. Eight studies did not report the target blood level of sirolimus [ 12 , 13 , 15 , 18 , 22 , 29 , 32 , 37 ]. Not in all studies the planned target trough level for sirolimus was achieved [ 14 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In one study each, 3.5–6 ng/mL [ 30 ], 4–8 ng/mL [ 21 ], 4–10 ng/mL [ 38 ], 4–13 ng/mL [ 36 ], 5–12 ng/mL [ 33 ], 10–12 ng/mL [ 27 ], 10–13 ng/mL [ 19 ] and 12–20 ng/mL [ 35 ] were the target concentrations. Eight studies did not report the target blood level of sirolimus [ 12 , 13 , 15 , 18 , 22 , 29 , 32 , 37 ]. Not in all studies the planned target trough level for sirolimus was achieved [ 14 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Akyüz et al [ 13 ] and Yesil et al [ 17 ] reported a decrease in size of 60% and 70% after 3 months, respectively. Gomez-Sanchez et al [ 34 ] reported a clinical response time from 3.5 to 9 months, Amodeo et al [ 20 ] reported about a response after two months of treatment, while Gonzalez-Hermosa et al [ 29 ] reported 13 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past decade, molecular classification of PROS has paved the way to several novel targeted treatment options derived from oncology57 including direct PIK3CA inhibitors,58 59 such as the alpha-specific Alpelisib (BYL719) recently used in a compassionate access scheme in PROS 26 60 61. Also drugs reducing oversignalling through the PI3K pathway have been successfully employed in PROS or related/overlapping conditions, such as miransertib (ARQ092), an oral, allosteric pan-AKT inhibitor62–66 or rapamycin, the first identified mTOR inhibitor 24 67–73…”
Section: Discussionmentioning
confidence: 99%